SIGNIFICANCE AND MODERN METHODOLOGICAL METHODS OF INCREASING ENVIRONMENTAL AWARENESS IN EDUCATIONAL INSTITUTIONS (American Journal of Pedagogical and Educational Research, 2025)
The article analyzes the relevance of ecological awareness formation in educational institutions, the role of modern methodological approaches in this regard. During the study, the state of environmental education was investigated using theoretical analysis, pedagogical observation, questionnaire and comparison methods. According to the results, the enrichment of traditional methods with modern technologies, interactive lessons, environmental projects and practical activities serves as an effective tool for raising students' environmental awareness. The author mentions the importance of integrated methods and digital tools in the development of environmental education.